Predicting emergency departments visit rates from septicemia in Taiwan using an age–period–cohort model, 1998 to 2012. Issue 50 (December 2016) - Tzeng, I-Shiang; Liu, Su-Hsun; Chiou, Yu Ting; Huang, Chien-Hsiung; Lee, Cheng-Jung; Chien, Cheng-Yu; Hsu, Shou-Chien; Weng, Yi-Ming; Chen, Kuan-Fu; Chen, Jih-Chang
Abstract : Abstract: The aim of this study was to determine the age–period–cohort (APC) effects on the rate of infection-related emergency department (ED) visits from septicemia for predicting the same in recent periods. In our study, we investigated the longitudinal trends in septicemia-related visit rates. Using an APC model to decompose the septicemia visit rates into the effects of age, time period, and cohort, and examine whether their effects varied by sex. The septicemia ED visit rate was classified as the International Classification of Disease Code 038 by primary and secondary diagnosis between 1998 and 2012. In both males and females, the visit rate of septicemia showed an increase from 2003 through 2012. An increase in septicemia visit rate after 2003 was observed in all age groups. An APC model indicated a reversal increasing period effect, which increased prominently from 2003 to 2012 in both males and females. The age effect showed an increasing trend. The cohort effect tended to show a slight oscillation from 1913 to 1988. With reference to the prediction of the logarithms of the age-specific 5-year visit rates, we observed that the younger cohorts exhibited a slightly increasing trend, as compared to the older cohorts. The period effect can explain the increase in septicemia visit rates, suggesting the role of screening for septicemia. Furthermore, it is well known that aging is a relevant risk variable for infectious diseases. The present study concludes that the aged population exhibited a strong increasing future trend for septicemia-related ED visit rates. Abstract : Supplemental Digital Content is available in the text